2018
DOI: 10.1039/c8nj01992d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthetic procedure to new 2-imino-1,3-thiazolines and thiazolidin-4-ones promoted by acetonitrile electrogenerated base

Abstract: Regioselective sulfur–carbon bond formation from disubstituted thioureas and 1,2-dielectrophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…[14,36,37] Several variant of the original synthetic method have been developed, like solid supported synthesis [14,38] base-catalyzed and aqueous methods. [39][40][41] Considering green chemistry principles and synthetic efficiency, we focused on one-pot and multicomponent approaches that have been designed by the in situ synthesis of thioureas or αhaloketones. Raja et al, Samimi et al and Heravi et al reported the preparation of 2-iminothiazolines in one-pot, based on the in situ generation of thioureas from amines and isothiocyanates followed by the ring annulation with 2'-bromoacetophenones (Scheme 1, eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,36,37] Several variant of the original synthetic method have been developed, like solid supported synthesis [14,38] base-catalyzed and aqueous methods. [39][40][41] Considering green chemistry principles and synthetic efficiency, we focused on one-pot and multicomponent approaches that have been designed by the in situ synthesis of thioureas or αhaloketones. Raja et al, Samimi et al and Heravi et al reported the preparation of 2-iminothiazolines in one-pot, based on the in situ generation of thioureas from amines and isothiocyanates followed by the ring annulation with 2'-bromoacetophenones (Scheme 1, eq.…”
Section: Introductionmentioning
confidence: 99%
“…The regioselectivity is driven by the p K a values of the NH protons, particularly the more basic nitrogen participates in the formation of the heterocycle [14,36,37] . Several variant of the original synthetic method have been developed, like solid supported synthesis [14,38] base‐catalyzed and aqueous methods [39–41] . Considering green chemistry principles and synthetic efficiency, we focused on one‐pot and multicomponent approaches that have been designed by the in situ synthesis of thioureas or α‐haloketones.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Haouas and co-workers 33 published a paper on the synthesis of thiazolines 70 and thiazolidin-4-ones 71 starting from N,N-disubstituted thioureas 68 and 1,2-dielectrophiles 69 (Scheme 42). A novel and convenient strategy for thiazole cycle was promoted by acetonitrile electrogenerated base (EGB) leading to the target compounds in III Fe…”
Section: Thiazolesmentioning
confidence: 99%
“…In the past two decades numerous papers reported direct oxidation of substrates such as amine derivatives to synthesize N ‐heterocycles, or direct electrolysis of benzoic acid derivatives to electrochemically synthesize O ‐heterocycles . On the other hand, the efficacy of strong basic species generated in situ through electrolysis of organic aprotic solvents (such as dimethyl sulfoxide, dimethylformamide, and acetonitrile) is well‐established, as is their application in organic synthesis for constructing N ‐heterocycles such as quinazolinones derivatives, imino‐1,3‐thiazolines, and imidazolidinones …”
Section: Introductionmentioning
confidence: 99%